TATA KELOLA DAN RISIKO BANK SYARIAH DI INDONESIA PERIODE 2008-2016 - Siti Mutmainah (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2018)
This study investigates the effect of corporate governance on Islamic bank’s risk in Indonesia during 2008-2016. The bank’s governance consists of board of commissioner (including risk control committe and audit committee), management, and sharia supervisory board. Because of the existence of these boards is a mandatory, hence this research focus on the amount of members and meetings in each board and committee. Results show that the amount of meetings held by management and risk control committee negatively influence the financing risk. This research implies the Islamic banks to strenghten their governance to control their banks’ risk. This research also recommends Central Bank and National Sharia Board to be more effective in performing its supervisory function.